Clinical Practice Guideline: Tinnitus Executive Summary. (October 2014) - Tunkel, David E.; Bauer, Carol A.; Sun, Gordon H.; Rosenfeld, Richard M.; Chandrasekhar, Sujana S.; Cunningham, Eugene R.; Archer, Sanford M.; Blakley, Brian W.; Carter, John M.; Granieri, Evelyn C.; Henry, James A.; Hollingsworth, Deena; et al.
The American Academy of Otolaryngology—Head and Neck Surgery Foundation (AAO-HNSF) has published a supplement to this issue featuring the new Clinical Practice Guideline: Tinnitus. To assist in implementing the guideline recommendations, this article summarizes the rationale, purpose, and key action statements. The 13 recommendations developed address the evaluation of patients with tinnitus, including selection and timing of diagnostic testing and specialty referral to identify potential underlying treatable pathology. It will then focus on the evaluation and treatment of patients with persistent primary tinnitus, with recommendations to guide the evaluation and measurement of the impact of tinnitus and to determine the most appropriate interventions to improve symptoms and quality of life for tinnitus sufferers.